A taxonomic revision of the South American species of Pseudocanthon Bates, 1887 (Coleoptera: Scarabaeidae: Scarabaeinae: Deltochilini) - Nazaré-Silva, Everton E.; Silva, Fernando A.b. (Zootaxa, 2021)
The South American species of Pseudocanthon Bates, 1887 (Coleoptera: Scarabaeidae: Scarabaeinae: Deltochilini) are reviewed. In this work, 10 valid species and two subspecies are recognized for the genus. Among these species, five are recorded in South America, including three new species: P. perplexus (LeConte, 1847), P. xanthurus (Blanchard, 1847), P. vazdemelloi new species, P. pantanensis new species, and P. chaquensis new species. A lectotype is designated for P. xanthurus (Blanchard, 1847). In this revision, each species is analyzed as follows: a detailed literature review, an identification key for the South American species, a diagnosis, descriptions, illustrations of key morphological characters, list of examined material, and geographic distribution.